FINANCIAL TRENDS ON FINANCIAL PERFORMANCE ASSESSMENT IN PUBLIC COMPANIES IN THE KAHYANGAN JEMBER PLANTATION AREA - Maulana, Anis; Yulliarti, Norita Citra; Nuha, Gardina Aulin (Universitas Muhammadiyah Tangerang, 2025)
This study uses trend analysis, this study took place at the Regional Public Company of Kahyangan Jember Plantation. Based on the formulation of the problem used, namely trend analysis using the base period of 2019 and the comparison period of 2020-2023, where the financial performance of the Regional Public Company of Kahyangan Jember Plantation is seen in terms of Profitability, Liquidity, Solvency and Activity ratios. Several sub-ratios used such as GPM, NPM, OPM, CR, QR, CaR, DAR, TIER, LIDtER, ITO, TATO, and DSO where the data in this study were obtained through the company itself with the period 2019-2023. This study is included in qualitative descriptive research with financial reports at the Regional Public Company of Kahyangan Jember Plantation. Based on the results of the analysis of financial reports using the trend method at the Regional Public Company of Kahyangan Jember Plantation in 2019-2023 for 5 years, it was concluded that during the 5-year period the company often experienced increases and even decreases in both cash flow and profit and loss reports. When viewed in terms of product sales in 2022, the largest was IDR 32,905,161,809.08, while when viewed in terms of operating assets, namely the company's debt in 2023, there was a significant decrease at IDR 91,982,875.00. Several account items at the Regional Public Company of Kahyangan Jember Plantation from 2019-2023 have quite significant differences in value.